2015
DOI: 10.2355/isijinternational.55.845
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Least Squares Support Vector Machine Predictor for Blast Furnace Ironmaking Process

Abstract: Blast furnace system is one of the most complex industrial systems and, as such, there are still many unsolved theoretical and experimental difficulties, such as silicon prediction. For this reason, based on recursive updating algorithm, an adaptive least squares support vector machine (LS-SVM) predictor is presented for prediction task of silicon content in blast furnace (BF) hot metal. The predicator employs recursive updating algorithm to get the precise solution of the latest LS-SVM model and avoid the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…According to Table 3 and Figure 5 , the magnitudes of the variables have big difference clearly. In fact, the effect of the variables with a large magnitude on the modeling is larger than the one with a small magnitude, thus it is not appropriate to directly take the data to establish the model [ 47 ]. Thus, all the data are normalized into (0, 1) with the same magnitude to eliminate the influence of dimension among variables before applying in the experiments.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…According to Table 3 and Figure 5 , the magnitudes of the variables have big difference clearly. In fact, the effect of the variables with a large magnitude on the modeling is larger than the one with a small magnitude, thus it is not appropriate to directly take the data to establish the model [ 47 ]. Thus, all the data are normalized into (0, 1) with the same magnitude to eliminate the influence of dimension among variables before applying in the experiments.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…In this case study, we compare the proposed BOKRR algorithm with online learning algorithm SWOKRR, BOLSSVM and batch-mode learning algorithm TIKRR. Gaussian kernel is specified as the kernel function for the compared algorithms for its good performance in applications [29]. The first 400 samples of two datasets are selected to form the initial active set.…”
Section: B Evaluation On a Real-world Application Problemmentioning
confidence: 99%
“…Table 1 illustrates the statistical properties of COD and BOD in respect of the divided training and testing sets, and Figure 2, it can be found that the data has the characteristics of violent fluctuation, and the magnitudes of the variables clearly display a big difference. In fact, the effect of the variables with a large magnitude on the modeling is larger than the one with a small magnitude, and thus it is not appropriate to directly take the data to establish the model [55]. Thus, all the data are normalized to (0, 1) with the same magnitude to eliminate the influence of the dimension among variables before applying them in the experiments.…”
Section: Data Setsmentioning
confidence: 99%